A importância da discriminação nas diferenças salarias: uma análise para o Brasil e suas regiões para os anos de 2002, 2006 e 2009 - Souza, Paola Faria Lucas de (2011)
Race and sex discrimination in the labor market is a poignant and important factor in determining income inequality in Brazil. This inequality has several determinants; among them are features that indicate the productivity of individuals, such as education and experience, and other features that are merely discriminatory, such as gender and race. The inequality caused by differences in productivity is identified in this work, the effect caused by endowment and the discriminatory effect of discrimination. The goal is to measure how much income inequality between race / gender groups can be explained by discrimination and difference in workers' skills, analyzing how these effects behave in different wage quintiles. For that purpose, the following methodology was used: probability curves, Oaxaca-Blinder decomposition (1973) and Machado and Mata decomposition (2005). The analysis was performed for Brazil as a whole and for the five Brazilian regions, using PNAD data for 2002, 2006 and 2009. The main results are: i) the most discriminated against group is nonwhite women, followed by white women and non-white men, ii) the probability curves for race and gender discrimination is shaped like a "U", and greater levels of discrimination are found in the first and last quintile, except for the South and Southeast regions, where discrimination grows with wage quintiles iii) a decrease in the wage gap is observed between groups in the 2002 to 2009 period; iv) the entire gender wage gap can be explained by discrimination, and effect endowment contributes to the wage gap decreasing, v) the higher the income quintile implies in discrimination having a larger role in gender differences, vi) on racial discrimination, both factors, discrimination and endowment act to increase the wage gap, vii ) the most important factor in determining the wage gap between racial groups is endowment; viii) the racial wage gap increases with the higher the quintile; ix) the higher the income, racial discrimination becomes less important in determining income differences considering Brazil as a whole, while the opposite is found in a regional level.